Application Of Continuous Improvement To Increase Productivity Line Cam Housing Assy C With PDCA Method - Wiharti Wiharti; Risti Yaningsih; Fransiskus Gea; Roni Suryo Suwarno; Tri Ngudi Wiyatno (DPPM Universitas Pelita Bangsa, 2024)
This study aims to determine the effect of the application of continuous improvement on the productivity of the Cam Housing Assy C line using the PDCA method. It is known that for the period of July 2021 November 2021, the achievement of the Cam Housing Assy C line productivity is the lowest. This research is a qualitative descriptive study and data collection techniques using interviews, documentation, and literature study. The Line Cam Housing Assy C has 7 man power with an average per shift producing 408.9 pcs, but there is still losstime. The most influential losstime on productivity is when preparing hatsumono (3.5%). To reduce the losstime, it is necessary to make improvements in the form of increasing efficiency by increasing the number of pcs/hour by each man power. Methods of data analysis using PDCA tools and Analysis of Muda, Mura, Muri. The results of this study were able to increase productivity from 8.43 Man.min/pcs to 6 Man.Min/pcs and increase the production line capacity from 408.9 pcs/shift to 470 pcs/shift.